Advancing an agenda for women in planning: an epilogue. Issue 1 (2nd January 2017) - Osborne, Natalie; Grant-Smith, Deanna; Bosman, Caryl
ABSTRACT: This paper serves as an epilogue to the Women in Planning special issue of Australian Planner reflecting on the potential for women's activism and scholarship to promote social and spatial change around what have often been dismissed as irrelevant private or personal matters. This paper highlights the energy and willingness among women planners and those sympathetic to their goals towards seeking and creative positive and transformative change and engagement with issues of gender in planning. It specifically reports on the Women in Planning Symposium, held in Brisbane in 2016, and based on the principles of Appreciative Inquiry. Through this case we do not set out to 'prove' the impact of feminist approaches to planning or Appreciative Inquiry as applied in this workshop, rather, our goal here is to conclude this special issue by advancing an agenda for women in planning which is transformative, generative and pro-feminist and which has the potential to highlight and address gendered concerns in a productive way. We will reflect on both the findings that Appreciative Inquiry yielded, and on the process itself as a tool for participation and engagement, particularly in a feminist/emancipatory context.